2021
DOI: 10.3389/fmats.2021.771941
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Doped Manganite Materials in Magnetic Refrigeration

Abstract: Magnetic refrigeration technology is a new, green, high-efficiency approach. It has attracted increasing attention from researchers and has a strong competitiveness over traditional refrigeration methods. With the continuous development of social lives, magnetic refrigeration technology must have important application prospects. This article briefly describes the basic principles. The focus is on the introduction and summary of research on perovskite manganite doping in magnetic refrigeration. Finally, the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Based on several studies, it can be concluded that A-site substitution with low-valence ions significantly influences changes in magnetic entropy and T C , often exhibiting extreme values that need to be considered for the effects of substitution in Mn 3+ /Mn 4+ in the material system. 18,77,117,119,121,143…”
Section: Phenomena and Parameters Influencing The Behavior Of Mce In ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Based on several studies, it can be concluded that A-site substitution with low-valence ions significantly influences changes in magnetic entropy and T C , often exhibiting extreme values that need to be considered for the effects of substitution in Mn 3+ /Mn 4+ in the material system. 18,77,117,119,121,143…”
Section: Phenomena and Parameters Influencing The Behavior Of Mce In ...mentioning
confidence: 99%
“…Substitution at the B-site involves replacing Mn ions with specific ions to tailor T C and increase the magnetic moment, which can enhance the value of −Δ S M . 18,137,144 The elements substituted at the B-site are transition metals (Ni, V, Fe, Co, Cr, and Cu). Al-Shahumi et al reported an investigation on La 0.7 Sr 0.3 Mn 1− x Fe x O 3 ( x = 0.0–0.30) compounds, where the T C values decreased from 370 to 98 K, accompanied by a decrease in the −Δ S M values from 1.83 to 0.13 J kg −1 K −1 .…”
Section: Phenomena and Parameters Influencing The Behavior Of Mce In ...mentioning
confidence: 99%
See 3 more Smart Citations